(untitled) (Atlas Journal of Biology, 2018)
Soybean (Glycine max (L.) Merr.) cultivars differ in their resistance to sudden death syndrome (SDS), caused by Fusarium virguliforme. Breeding for improving SDS response has been challenging, due to interactions among the 18-42 known resistance loci. Four quantitative trait loci (QTL) for resistance to SDS (cqRfs–cqRfs3) were clustered within 20 cM of the rhg1 locus underlying resistance to soybean cyst nematode (SCN) on Chromosome (Chr.) 18. Another locus on Chr. 20 (cqRfs5) was reported to interact with this cluster. The aims here were to compare the inheritance of resistance to SDS in a near isogenic line (NIL) population that was fixed for resistance to SCN but segregated at two of the four loci (cqRfs1 and cqRfs) for SDS resistance; to examine the interaction with the locus on Chr. 20; and to identify candidate genes underlying QTL. Used were; a NIL population derived from residual heterozygosity in an F5:7 recombinant inbred line EF60 (lines 1-38); SDS response data from two locations and years; four segregating microsatellite and 1,500 SNP markers. Polymorphic regions were found from 2,788 Kbp to 8,938 Kbp on Chr. 18 and 33,100 Kbp to 34,943 Kbp on Chr. 20 that were significantly (0.005 < P > 0.0001) associated with resistance to SDS. The QTL fine maps suggested that the two loci on Chr. 18 were three loci (cqRfs1, cqRfs, and cqRfs19). Candidate genes were inferred. An epistatic interaction was inferred between Chr. 18 and Chr. 20 loci. Therefore, SDS resistance QTL were both complex and interacting.